Evaluation of electrochemical monitors for atmospheric corrosion studies of carbon steel - Garita-Arce, Luis (2014)
In the current study, it is the objective to evaluate different types of electrochemical monitors for stu-dies of atmospheric corrosion. In order to achieve such objective, runs were carried out in the zero state of the specimens, under controlled relativity humidity and temperature. Furthermore, runs were carried out over time and with hydrophilic activated samples. The used electrochemical techniques were: the linear polarization resistance (LPR) and the electrochemical noise (ECN,) which have as response variables the polarization resistance (RP) and the noise resistance (RN) respectively. Among the main conclusions, it is that the specimen of three identical electrodes and the comb type one of three electrodes show better results in regards to variations of relative humidity (RH.) However, it is recommended new comb shaped electrodes where the distance between them is less in order to study them by comparing such electrodes with the three identical ones.